2009
DOI: 10.3347/kjp.2009.47.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii Infection and Characteristics of Seropositive Patients in General Hospitals in Daejeon, Korea

Abstract: To figure out the epidemiological status and relevance with other diseases in toxoplasmosis, we checked serum IgG antibody titers of 1,265 patients and medical records of seropositive patients. Seropositive rates were 6.6% by latex agglutination test (LAT) and 6.7% by ELISA. No significant differences were detected between sexes and age groups. The peak seroprevalence was detected in the 40-49-year-old age group. According to clinical department, Toxoplasma-positive rates were high in patients in psychiatry, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 16 publications
(40 reference statements)
5
55
2
2
Order By: Relevance
“…The global seroprevalence in humans and animals varies greatly among countries, ranging from 6.7% in Korea to 68.6% in Brazil, depending on the geographical location and differences in lifestyle [2][3]. The authors of a previous systematic review of the Iranian general population estimated that approximately 39.3% (95% CI, 33.0 to 45.7) of individuals were seropositive [4].…”
Section: Introductionmentioning
confidence: 99%
“…The global seroprevalence in humans and animals varies greatly among countries, ranging from 6.7% in Korea to 68.6% in Brazil, depending on the geographical location and differences in lifestyle [2][3]. The authors of a previous systematic review of the Iranian general population estimated that approximately 39.3% (95% CI, 33.0 to 45.7) of individuals were seropositive [4].…”
Section: Introductionmentioning
confidence: 99%
“…As such, these ELISAs may be used as a marker for active Toxoplasma infection in IC patients (429). A latex agglutination test (519) and several other ELISAs are also available for the detection of anti-Toxoplasma antibodies (2,338,519,613).…”
Section: Toxoplasma Gondiimentioning
confidence: 99%
“…In Brazil, toxoplasmosis is an important public health problem in many areas, with serological prevalence ranging from 50-84% for T. gondii infection in adults (Bahia-Oliveira et al, 2003;Spalding et al, 2005). Shin et al (2009) reported that the recent seroprevalence of T. gondii ranges from 0.79-12.9% in the Korean population. In Turkey, it was reported to be 36% in Kayseri (Zamani et al, 2007) reported that T. gondii infection has shown considerable prevalence in Iran and seropositivity ranges from 5.7-87%.…”
Section: Introductionmentioning
confidence: 99%